ACTIVISTS’ POLITICAL PURGE IN (AND THROUGH) THE ARGENTINIAN STATE (1973-1983) - D'Antonio, Débora Carina (Revista de Historia Social y de las Mentalidades, 2024)
This article examines the legislation the Argentinian State applied on a sector of the working class employed in public agencies and companies, with the aim of “debugging” it, ideologically speaking. The dispensability’s laws from 1973 and 1976 and the ones of national security from 1974 and 1976 that resulted in layoffs, casualties, dismissals or forced resignations offered the legal frame and the necessary legitimacy to carry out that control and persecution. This text proposes an analysis focused in the way different de facto and constitutional regimes made use of these normatives. In the years of the peronist government (1973-1976) the expulsion was destined to whom showed a high level of political and syndical autonomy, as the witness case that is investigated by Industrias Mecánicas del Estado (IME). Since the last military dictatorship (1976-1983), the dismissal combined with the physical coercion to the point of becoming a prelude to the forced disappearance of numerous activists.
Keywords: Working class; Political Purge; State Repression; Recent Argentine Past